A Simulation Study for Optimal Pinhole Collimator Design in Gamma Camera Systems - M. A. Ghoneim (Journal of Medical Physics)
Background: The usage of a semiconductor detector with a pinhole collimator can provide high spatial resolution due to its high intrinsic resolution. However, the collimator system has low sensitivity due to the hole’s small diameter. Therefore, the optimization between the spatial resolution and sensitivity is critical for determining the image quality in the gamma camera system. Aims and Objectives: A pinhole collimator was designed and simulated to achieve the desired level of resolution and sensitivity in a gamma camera by utilizing a CdTe semiconductor detector. Materials and Methods: To conduct this objective, a simulation toolkit based on the Geant4 Application for Tomographic Emission (GATE) was employed. The imaging capabilities of the proposed system were assessed by varying the magnification factor and pinhole diameter to estimate spatial resolution and sensitivity. Moreover, a hot rod phantom was designed to evaluate the system’s overall imaging functionality. Results: Results revealed that an increase in the pinhole diameter was correlated with an increase in sensitivity, while the spatial resolution was decreasing. There were distinct variations in sensitivity and spatial resolution depending on changes in the magnification factor as well. Finally, by analyzing trade-off curves, 1.38±0.081 mm was approximately the optimal pinhole diameter for our proposed system. Conclusion: The optimum position for a pinhole collimator with a CdTe semiconductor detector was demonstrated.